ERROR ANALYSIS GEOMETRY QUESTIONS ON WORKING CLASS V SD / MI IN YOGYAKARTA - Endang Sulistyowati (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2015)
In 2013, the results of UAN for mathematics in primary schools / MI in DIY average value is lower than other subjects, namely Indonesian and IPA. The success of the sixth grade students work on problems UAN is inseparable from the ability of students to understand math at grade material underneath. Based on the experience of researchers, many teachers who have less correct geometry concepts. Of course this is an impact on students' understanding of geometrical concepts. So in this study will be examined whether the errors are mostly done by students in grade V on the geometry of the material, especially material area and perimeter of a flat wake. This research is qualitative descriptive field. Subjects were 43 fifth grade students who come from 4 SD / MI in the city of Yogyakarta. Data retrieval by providing written test questions, the essay form. The results showed that the most frequent errors are errors of type-1, which is a misconception. Another error is the fault of type-3, namely: writing mathematical notation and use of the unit.